About capital and ideology by Thomas Piketty - JinHyo Joseph Yun (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study reviews Thomas Piketty's Capital and Ideology and provides a detailed analysis to aid understanding of the book, combined with diverse scholars' perspectives in the fields of economic history, political economics, and social sciences. This book is selected as my review target to answer the following research question, 'How do we conquer the growth limits of capitalism?' This book gave me several ideas for the basis of my future research. In this review paper, I provide a guide for readers to understand ways to conquer the growth limits of capitalism. My study also provides a creative understanding of the evolution of the capitalist economy from new perspectives. In particular, it presents an analysis of Piketty's diverse policy ideas from the viewpoint of a global history of capitalism. This will give a new lens through which to focus on understanding and resolving the inequalities of 21st-century hyper-capitalism and to construct policy for the current world economy. Finally, this study offers a causal loop model of Piketty's findings and proposals, and suggests future research topics.
Keywords: 650; inequality; ownership society; progressive tax; social nativism; social ownership; trifunctional society